Empowerment of Elderly Posyandu Cadres of Kauman Village, Malang City in Making Healthy Snacks with Dragon Fruit Yogurt - Andika, Venny Kurnia; Luluk Anisyah; Nancy Ratu Jovancha Laurentza (Transformatif : Jurnal Pengabdian Masyarakat, 2025)
The elderly need special attention to their nutritional intake. However, elderly posyandu cadres often have difficulties in determining the type of additional food that suits the needs of the elderly, and do not have the skills to process daily food ingredients into healthy snacks. Yogurt is a type of healthy snack that is beneficial for the health of the elderly. This activity aims to increase the knowledge of elderly posyandu cadres about healthy snacks and how to make dragon fruit yogurt as one of the alternative healthy snacks for the elderly. The method used is Participatory Action Research (PAR), which is designed to answer partner problems through a participatory approach. The activity was attended by 19 elderly posyandu cadres. Evaluation was carried out through pre-test and post-test to measure the level of understanding of participants. This program is carried out in three stages, namely the presentation about healthy snacks knowledge, training on how to make dragon fruit yogurt, and direct manufacturing practices. The results of the evaluation showed an average score increase of 66.5% between pretest and post-test, which showed that the information and skills provided could be well received and understood by the participants, as well as indicating the success of this service activity.